Patients with a transabdominal cerclage due to recurrent mid-trimester losses are not at higher risk of foetal growth restriction: a retrospective study - David R. Hall; Lana Koster; Mari van de Vyver (Journal of Obstetrics and Gynaecology)
Foetal growth restriction (FGR) is associated with neonatal morbidity, suboptimal neurodevelopmental outcomes and chronic diseases. Successful pregnancies of women with recurrent mid-trimester pregnancy losses may still be at risk of FGR and small for gestational age (SGA) outcomes. This study aimed to investigate whether patients with recurrent mid-trimester pregnancy losses who undergo transabdominal cerclage (TAC) are at an increased risk of FGR. Due to a paucity of information in this regard, and to inform accurate counselling, we performed a secondary analysis of a unique set of patients with a TAC procedure. Foetal growth restriction (<3rd centile) was present in 8% of cases, with more female than male babies falling in this category (9.2 vs. 7.4%). When combined, FGR plus SGA were present in 19.4% of cases. This rate is not higher than the expected population rate of around 20% in low- and middle-income countries.